Effects of Growth Stage and Physiological State on Gut Health, Antioxidant Capacity, and Muscle Nutritional Composition in Greenhouse-Cultured Pelodiscus sinensis - Qingman Yang; Yuhong Liao; Huihui Quan; Qing Qiu; Huahua Mao; Dachun Gong; Xuan Tu; Zirui Wang; Hao Fu; Xionge Pi (Antioxidants, 2026)
The production performance, muscle quality, and gut microbiota of aquatic animals are closely associated with host growth stage and disease status. This study therefore compared the gut health, antioxidant capacity, and muscle nutritional composition of greenhouse-cultured Pelodiscus sinensis covering two growth stages (juvenile and adult) and two physiological states (healthy and diseased). The results showed that healthy turtles possessed significantly longer and denser intestinal villi compared with diseased turtles (p < 0.01), and adult turtles maintained higher activities of glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and lysozyme (LZM) than juveniles regardless of health condition. Digestive enzyme profiles varied with age and health. Compared with adult turtles, juveniles exhibited significantly higher trypsin activity in both healthy and diseased groups (p < 0.001). Conversely, juveniles displayed significantly lower lipase activity than adults in the diseased group (p = 0.008). For muscle nutritional composition, adults contained higher crude protein (CP), essential amino acids (EAAs), and umami amino acids (UAAs) than juveniles, while healthy turtles had significantly better muscle quality indices than diseased individuals (p < 0.05). Meanwhile, gut microbial composition differed significantly between growth stages and health states (p = 0.001). The relative abundance of unclassified_f_Lachnospiraceae and Clostridium_sensu_stricto_2 was positively correlated with GSH-Px and muscle nutritional composition indicators (CP, EAAs, and UAAs), whereas it was negatively correlated with liver alkaline phosphatase (ALP), acid phosphatase (ACP), and intestinal enzyme activities. Data also showed that unclassified_o_Bacteroidales and unclassified_f_Lachnospiraceae may affect muscle nutritional composition and non-specific immunity by regulating the microbial functional pathways of amino acid metabolism, the digestive system, and non-specific immunity system. Collectively, these observations offer insights into variations in physiological traits of greenhouse-cultured P. sinensis. These correlational findings suggest that gut microbiota are closely associated with muscle nutrition and antioxidant status, providing valuable insights for sustainable soft-shelled turtle aquaculture.